Enrique Melaka @ Panglima Awang sebagai Magellan Melayu - Nik Hassan Shuhaimi Nik Abd. Rahman,; Shaiful Bahri Md. Radzi,; Khazin Mohd. Tamrin,; Yahaya Abu Bakar, (Universiti Kebangsaan Malaysia, 2009)
This article attempts to deliberate on the pioneering effort in circumnavigating the globe by sailing during the 16th century. The West conferred this honour on Ferdinand de Magellan, while the Spanish claimed that it was Sebastian del Cano who accomplished this calling of sailing around the world. But in reality, it was Enrique of Malacca who was the first person to circumnavigate the earth, by completing a 360 degree voyage in nine years, ahead of other sailors’ achievements, including Magellan and del Cano. Enrique’s success received much acclamation for he demonstrated much skill in navigation. This has been well-narrated in Harun Aminurrashid’s novel titled Panglima Awang. When compared with other Melaka warriors who fought against the Portuguese, Enrique was only a youth at that time and was kept captive after the fall of Malacca in 1511. As a war captive and later a loyal slave to Magellan, Enrique ventured the waters of the world. Although he never returned to Melaka, he eventually managed to reach the Malay territory where the lingua franca was the Malay language. Enrique knowledge in voyaging the mighty oceans of the world, besides his devoted loyalty to his master, definitely indicates his ethnic origins as a Orang Laut, a tribe that was known to be the great sea-farers in the 16th century. His victorious accomplishment in navigation should make Enrique of Melaka Magellan, a Malay one, i.e., the first person to sail round the world